Jag1 insufficiency alters liver fibrosis via T cell and hepatocyte differentiation defects - Mašek, Jan; Filipovic, Iva; Van Hul, Noémi; Belicová, Lenka; Jiroušková, Markéta; Oliveira, Daniel V; Frontino, Anna Maria; Hankeova, Simona; He, Jingyan; Turetti, Fabio; Iqbal, Afshan; Červenka, Igor; et al. (EMBO molecular medicine, 2024)
Fibrosis contributes to tissue repair, but excessive fibrosis disrupts organ function. Alagille syndrome (ALGS, caused by mutations in JAGGED1) results in liver disease and characteristic fibrosis. Here, we show that Jag1Ndr/Ndr mice, a model for ALGS, recapitulate ALGS-like fibrosis. Single-cell RNA-seq and multi-color flow cytometry of the liver revealed immature hepatocytes and paradoxically low intrahepatic T cell infiltration despite cholestasis in Jag1Ndr/Ndr mice. Thymic and splenic regulatory T cells (Tregs) were enriched and Jag1Ndr/Ndr lymphocyte immune and fibrotic capacity was tested with adoptive transfer into Rag1-/- mice, challenged with dextran sulfate sodium (DSS) or bile duct ligation (BDL). Transplanted Jag1Ndr/Ndr lymphocytes were less inflammatory with fewer activated T cells than Jag1+/+ lymphocytes in response to DSS. Cholestasis induced by BDL in Rag1-/- mice with Jag1Ndr/Ndr lymphocytes resulted in periportal Treg accumulation and three-fold less periportal fibrosis than in Rag1-/- mice with Jag1+/+ lymphocytes. Finally, the Jag1Ndr/Ndr hepatocyte expression profile and Treg overrepresentation were corroborated in patients' liver samples. Jag1-dependent hepatic and immune defects thus interact to determine the fibrotic process in ALGS.
Keywords: Hepatocytes; Treg; protein jagged-1; Cell Differentiation; Fibrosis; Alagille Syndrome; Alagillův syndrom; Alagille syndrome; jaterní cirhóza; Disease Models, Animal; myši inbrední C57BL; Notch; Liver Cirrhosis; regulační T-lymfocyty; Mice; myši knockoutované; T-Lymphocytes, Regulatory; hepatocyty; modely nemocí na zvířatech; zvířata; Humans; Jagged1; Mice, Knockout; myši; Jagged-1 Protein; buněčná diferenciace; Mice, Inbred C57BL; lidé; Animals